What can work and how? An overview of evidence-based interventions and delivery strategies to support health and human development from before conception to 20 years. Issue 10337 (7th May 2022) - Vaivada, Tyler; Lassi, Zohra S; Irfan, Omar; Salam, Rehana A; Das, Jai K; Oh, Christina; Carducci, Bianca; Jain, Reena P; Als, Daina; Sharma, Naeha; Keats, Emily C; Patton, George C; et al.
Summary: Progress has been made globally in improving the coverage of key maternal, newborn, and early childhood interventions in low-income and middle-income countries, which has contributed to a decrease in child mortality and morbidity. However, inequities remain, and many children and adolescents are still not covered by life-saving and nurturing care interventions, despite their relatively low costs and high cost-effectiveness. This Series paper builds on a large body of work from the past two decades on evidence-based interventions and packages of care for survival, strategies for delivery, and platforms to reach the most vulnerable. We review the current evidence base on the effectiveness of a variety of essential and emerging interventions that can be delivered from before conception until age 20 years to help children and adolescents not only survive into adulthood, but also to grow and develop optimally, support their wellbeing, and help them reach their full developmental potential. Although scaling up evidence-based interventions in children younger than 5 years might have the greatest effect on reducing child mortality rates, we highlight interventions and evidence gaps for school-age children (5–9 years) and the transition from childhood to adolescence (10–19 years), including interventions to support mental health and positive development, and address unintentional injuries, neglected tropical diseases, and non-communicable diseases.